'Save the planet, plant a tree!': REDD+ and global/local forest governance in the Anthropocene. Issue 3 (2nd September 2017) - Müller, Franziska
Abstract: The age of the Anthropocene has developed unique forms and practices of earth system governance, i.e. ways of governing nature and populations on a global/local scale claiming to offer holistic, borderless forms of global/local cooperation that bridge nature/culture/society divides and seek to create a universalised, 'planetary' actorness. With regard to climate change adaptation, this actorness is increasingly stretched out to the postcolonial sphere, including small-scale farmer communities, forest-dwellers and indigenous communities, who are all addressed as responsible subjects through the IPCC's Reducing Emissions from Deforestation and Degradation (REDD+) measures. As a powerful instrument of global climate governance, REDD+ programmes create highly complex regimes, thereby totalising the principle of liberal 'stakeholder governance'. This article addresses REDD+ as a specific case of 'Anthropocene geopolitics' that have discovered 'the local' as a site of powerful ecological intervention, taking place in a postcolonial setting. Based on an analysis of inter/transnational REDD+ funds, their activities, outcomes and forms of governing nature and populations, the aim is to identify distinct political technologies that orchestrate the REDD+ regime and discuss how they reshape nature-society relations in the Anthropocene.